Mitochondrial and nuclear gene expression for cytochrome oxidase subunits are disproportionately regulated by functional activity in neurons - Hevner, RF (J Neurosci, 1993)
Mitochondrial respiratory complexes such as cytochrome oxidase (CO) contain both mitochondrial- and nuclear-encoded subunits. To determine whether mitochondrial and nuclear gene expression are regulated proportionately in neurons, we analyzed CO subunit mRNA and mitochondrial DNA (mtDNA) levels by in situ hybridization and grain counting in the visual system of normal and monocular TTX-treated monkeys. We compared the regulation of these molecules with the regulation of CO activity and CO protein, analyzed by histochemistry and immunohistochemistry, respectively. In normal animals, CO activity was in general related more closely to mtDNA and CO subunit I (COI) (mitochondrial-encoded) mRNA levels than to COIV or COVIII (nuclear- encoded) mRNA levels. For example, puffs (also known as blobs) of high CO activity in striate cortex were enriched in mtDNA and COI mRNA, but not COIV or COVIII mRNA. In 3–7 d TTX-treated animals, proportionate decreases in CO activity and CO protein were observed in specific visual centers; these changes were accompanied by disproportionate decreases in COI, COIV, and COVIII mRNA levels. After 7 d of TTX, COI mRNA fell by 49 +/- 3% (mean +/- SEM) in LGN neurons, while COIV and COVIII mRNAs fell by only 18 +/- 3% and 29 +/- 3%, respectively. In comparison, CO activity decreased by 23 +/- 2%, and mtDNA by 26 +/- 4%. Qualitative observations in striate cortex also indicated that COI mRNA changed more than COIV mRNA, COVIII mRNA, mtDNA, or CO activity. Our results suggest that the local distribution of CO within neurons, and acute regulatory changes in CO activity occurring over periods of days are controlled mainly by regulation of the mitochondrial genes that encode the catalytic subunits of the enzyme.